MENGGALI KONSEP SELF HEALING DALAM AL-QUR'AN - Jannatul Aulia; Bashori (CV. Adiba Aisha Amira, 2024)
This study aims to examine the concept of self healing in the Qur'an and how the teachings of the Qur'an can be used as a tool for self-recovery. Self healing, or self-recovery, is an approach that helps individuals manage emotions and improve mental and spiritual well-being without external intervention. Through thematic tafsir (maudu’i) analysis of verses related to healing, this study explores the importance of faith, patience, gratitude, and worship in the self healing process. The results of the study show that the Qur'an provides comprehensive guidance for achieving self healing through strong faith, prayer and worship, resilience in facing life's challenges, and gratitude. These teachings not only provide spiritual support but also help individuals cope with stress and improve overall quality of life. This research contributes to a deeper understanding of the integration of psychological and spiritual approaches in self healing, and provides practical insights for individuals and health practitioners seeking alternative methods for enhancing well-being